A Comprehensive Review on Nutrient Profile and Pharmacological Benefits of Musa paradisiaca - Jaleel, Abdul K.; Jacob, Sapna; Ghosh, Suresh Mohan; Suresh, Amritesh (Sciences of Phytochemistry, 2024)
The Banana (Musa paradisiaca Linn., Family: Musaceae) is one of the oldest and most widely cultivated fruit plants, dating back to prehistoric times. Bananas are rich in minerals and phytochemicals, contributing to their significant culinary, nutritional, and medicinal properties. This review analyzes 191 peer-reviewed articles published between 1981 and July 2023 to comprehensively assess the health benefits of bananas. Studies highlight their effectiveness in reducing inflammation, cancer, diabetes, depression, diarrhea, urolithiasis, and ulcers. Additionally, bananas exhibit antibacterial, antiviral, antihyperlipidemic, antiatherosclerotic, hepatoprotective, hair-growing, wound-healing, and antihypertensive properties. The articles were sourced from databases such as PubMed, Scopus, and Google Scholar using keywords like Musa paradisiaca, health benefits, inflammation, cancer, diabetes, and phytochemicals. Inclusion criteria included original research, clinical trials, in vitro and in vivo studies, and reviews focused on banana’s medicinal properties, while non-peer-reviewed papers and studies not directly related to Musa paradisiaca were excluded. This review reinforces the comprehensive health-promoting benefits of bananas and sets the stage for future research, which should focus on large-scale clinical trials, phytochemical standardization, and sustainable utilization of banana plant components. Bananas hold immense potential as both a functional food and a medicinal plant, making them a promising subject for future studies in nutraceuticals and sustainable agriculture.